Verifying the Best Iraqi Area to Install a LOFAR Radio Telescope Using SWOT Model - Kahdim, Zina Fadel; Abood, Kamal M. (Iraqi Journal of Science, 2024)
Many of the radio telescope’s wireless sensor networks operate outdoors, where changing weather might impact their system performance. Therefore, it is necessary to explore the climatic and topographic factors that affect the quality of the radio link to mitigate its impact and adapt to different conditions. In this study, the effects of the region’s topography and climate on the strength of the radio signal were studied. Besides studying the effects of the soil of the area and land flatness on determining the optimal location for erecting a radio telescope in Iraq within four governorates (Nineveh, AL-Anbar, Al-Najaf, and Al-Muthanna). Data from relevant ministries and a digital map dataset for the area’s topography with dimensions of 4 km x 6 km were used. The obtained results, via applying the SWOT model, showed that the best Iraqi area for erecting a radio telescope (LOFAR) among the selected regions according to the atmospheric parameters, such as air temperature, relative humidity, and wind speed, and other conditions such as transportation, the security component, number of buildings, population, and communication towers was Al- Muthanna governorate. It is considered the best radio zone for observing radio signals.